Thermal Comfort & Its Relation To Ventilation Approaches In The Main Prayer Hall Of Mosque & Hostel Room, USM Engineering Campus - Husain, Sharmira (Universiti Sains Malaysia, 2022)
This study was conducted to determine users' satisfaction with the building's indoor environment. This study was performed at the main prayer hall of Pusat Islam Engineering Campus, USM and the hostel room in Desasiswa Lembaran (SH2). It involved determining whether the thermal comfort standards were being met, which included the air temperature and relative humidity. The data were measured using Temperature- Relative Humidity (T-Rh) Data Logger, and the result was downloaded using T-Rh software. The Center for the Built Environment (CBE) Thermal Comfort Tool is then used to input the parameters to calculate the Predicted Mean Value (PMV) and Predicted Percentage Dissatisfied (PPD) for ASHRAE Standard-55. The parameters inserted are air temperature, relative humidity, air velocity, metabolic rate and clothing level. The PPD value shows the percentage of dissatisfaction. The PMV and PPD value results were compared with the Industry Code of Practice (ICOP) 2010 standard limit. The monitoring for this study was conducted for two sessions on a day, 1 P.M – 2 P.M. and 5 P.M. -6 P.M. for both locations with minute intervals. The highest temperature recorded in the mosque is 33.7°C, monitoring at 1 P.M -2 P.M. (Day 1). For monitoring in the hostel room, the highest PMV and PPD values obtained were 1.6 and 57%, respectively. Overall, the results indicate that most thermal comfort parameters measured do not comply with the ICOP standard limit, whereby the PMV is not within the range of -0.5 <PMV< +0.5 and PPD is >10%. This is due to poor façade design and inadequate building ventilation systems.